Religious Extracurricular Activities and Students’ Understanding of Islamic Teachings: A Study at SMP Negeri 1 Tolitoli - Auliya Nurul Marfuah; Kasmiati Kasmiati; Jumri Hi. Tahang Basire (Civiliza Publishing, 2026)
Religious extracurricular activities are one of the school’s strategies for strengthening students’ understanding of Islamic teachings and fostering their religious character. This study aims to analyze the implementation of religious extracurricular activities and the factors influencing their effectiveness at SMP Negeri 1 Tolitoli. The study employs a qualitative approach using observation, interviews, and documentation. The results indicate that activities such as congregational Dhuha prayer, short-term Islamic boarding school programs, large-scale zikir (remembrance of God), and calligraphy contribute to enhancing students’ understanding of Islamic teachings, discipline, and religious attitudes. The findings reveal that the effectiveness of these activities is more determined by the synergy between the school, Islamic Education teachers, the Student Council (OSIS), and active student participation than by the mere implementation of religious programs. Supporting factors include school support, teacher guidance, and student enthusiasm, while inhibiting factors include time constraints, conflicts with academic schedules, and the suboptimal implementation of some programs. This study contributes to demonstrating that religious extracurricular activities can serve as an integrative means to enhance students’ understanding of Islamic teachings while simultaneously fostering their religious character.